2021
DOI: 10.1109/access.2021.3088901
|View full text |Cite
|
Sign up to set email alerts
|

Guaranteeing Correctness of Machine Learning Based Decision Making at Higher Educational Institutions

Abstract: State-of-the-art software technologies have enabled Higher Education Institutions to record and store large amounts of student data. Analyzing this large amount of data can facilitate the decisionmaking process. Decisions made in higher education institutions affect policies, strategies and actions that improve education quality. It can be argued that machine learning algorithms demonstrate a remarkable ability to recognize models and predict results based on data. However, machine learning outcomes were subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Table 4 summarizes the papers analysed, including information about the AI applied, who used the AI, and what main benefits it provided. In brief, the results revealed that the main advantages of AI applications in higher education were to improve educational outcomes [3,7,12,16,18,22,27,29,30,32], to enhance institutional decision-making [1,8,14,21,26], and to advance institutional systems [2,10,23]. Moreover, the end users benefiting from the AI applications mainly were higher education institutions (n=11), instructors (n=9), and college students (n=6).…”
Section: Advantages and Disadvantages Of Using Aimentioning
confidence: 99%
“…Table 4 summarizes the papers analysed, including information about the AI applied, who used the AI, and what main benefits it provided. In brief, the results revealed that the main advantages of AI applications in higher education were to improve educational outcomes [3,7,12,16,18,22,27,29,30,32], to enhance institutional decision-making [1,8,14,21,26], and to advance institutional systems [2,10,23]. Moreover, the end users benefiting from the AI applications mainly were higher education institutions (n=11), instructors (n=9), and college students (n=6).…”
Section: Advantages and Disadvantages Of Using Aimentioning
confidence: 99%
“…Computational algorithms and automated decision support systems (DSS) may enhance this manual process. DSSs have shown tremendous success in automating processes and supporting human decisions in different domains, such as in higher education, health care [ 22 ], education [ 23 ], agriculture [ 24 , 25 ], and finance [ 26 ]. These DSSs benefit from artificial intelligence and machine learning techniques that can identify patterns and use them in their decision-making process.…”
Section: Discussionmentioning
confidence: 99%
“…The simulated scenarios demonstrate the effectiveness of the strategy. Nauman et al (2021) asserts that organizations may gather and store vast volumes of student data using cutting-edge technologies. This quantity of knowledge might aid in making a decision.…”
Section: Detailed Review Of Existing Decision Recommendation Modelsmentioning
confidence: 99%